Australian General Sonographers' Perceptions on Their Continuing Professional Development Learning Needs: A Descriptive Study - Lida Baynes; Sandra Carr; Kiah Evans (Australasian Journal of Ultrasound in Medicine, 2026)
ABSTRACT Introduction Continuing Professional Development (CPD) is essential for maintaining and enhancing the clinical competencies of sonographers. Despite its mandatory nature, factors influencing CPD participation among general sonographers in Australia remain underexplored. Aim This study aimed to explore general sonographers' perceptions of their CPD learning needs and to identify the barriers and facilitators influencing their CPD participation. Methods A two‐phase descriptive study was conducted. Phase one involved a scoping literature review on CPD barriers and facilitators among health professionals, guided by the Joanna Briggs Institute Population (or Participants), Concept, and Context (JBI PCC) framework. Phase two involved a cross sectional online survey of Australian general sonographers, utilising mixed methods to capture quantitative and qualitative data. Quantitative data were analysed using descriptive statistics, and qualitative data were analysed thematically. Results A total of 233 general sonographers commenced the survey, of whom 126 completed it. Sonographers strongly recognised the importance of CPD, with technical CPD rated as more beneficial and relevant than non‐technical CPD. Specialised webinars, workshops, conferences and case reviews were highly valued. Preferred delivery methods included small group in‐person workshops and on‐the‐job training. Major barriers included financial costs, time constraints, workload and personal commitments. Facilitators included flexible access, employer support and relevance of CPD content. Discussion Sonographers prioritised skill‐based, flexible and practical CPD formats but faced persistent financial and time‐related barriers. Organisational support and targeted CPD delivery methods could significantly improve participation. Conclusion Sonographers value CPD but face participation barriers; greater employer support and flexible delivery can improve engagement and professional development.